Software portability. - Lecarme, Olivier; Pellissier Gart, Mireille (New York, United States of America : McGraw-Hill, Inc., 1986)
"A much-needed text that presents for the first time the essential theory, methods, and techniques needed to understand and achieve successful software portability. A professional reference tool and an authoritative teaching manual designed to give software developers, amateur and professional programmers, and computer science students the capability to. • Evaluate the portability of various software products using more precise and uniform criteria • Select the most effective method for implementing new portable software. • Develop a program that meets current job requirements and is capable of being transported to a different system for future projects. • Cut the cost of new software development and increase the life span of a program's effectiveness. • Produce software that provides for more efficient use and greater range of applicability. • Investigate promising new areas of software portability." (Copied from the back cover).
Preface. Chapter 1. Introduction. Part 1. The bases of portability. Chapter 2. The major problems in software Portability. Chapter 3. Software tools of transport. Chapter 4. Linguistic means of transport. Chapter 5. Language-implementation methods. Parte 2. Case studies. Chapter 6. Translators and interpreters. Chapter 7. Operating and programming systems. Chapter 8. Conclusion. Bibliography. Index.
Bibliography: p. 198-215
Keywords: SOFTWARE COMPATIBILITY; SOFTWARE DEVELOPMENT; OPERATING AND PROGRAMMING SYSTEMS; COMPUTER SCIENCE; COMPUTER PROGRAMMING; PROGRAMMING LANGUAGE